2024
DOI: 10.1111/os.13976
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Predictor of the Length and Size of ACL Grafts in Chinese Han Adults for ACL Reconstruction: An MRI Study

Qingjun Yang,
Wenqian Lu,
Yong Luo
et al.

Abstract: ObjectiveCurrently, there is no simple and valid method to predict the length and size of the native anterior cruciate ligament (ACL) in each adult patient who will undergo ACL reconstruction. This study aimed to develop an imaging prediction method that can predict the length and size of ACL grafts using the intact posterior cruciate ligament (PCL), in order to enhance the graft preparation individualized sizing.MethodsThree hundred and nineteen patients aged 18 years or older who underwent magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These outcomes suggest that 6HS autografts are robust and durable, capable of withstanding the demands of daily activities and sports, thus enabling a more efficient and potentially faster rehabilitation process [33][34][35][36]. For instance, Yang et al [14] observed very low re-injury rates and high functional outcomes with 6HS autografts, emphasizing their clinical effectiveness. Additionally, recent studies, such as those by Chen et al [37], corroborated these findings, noting the biomechanical advantages and positive patient-reported outcomes associated with these larger grafts.…”
Section: Long-term Outcomes and Complicationsmentioning
confidence: 97%
See 2 more Smart Citations
“…These outcomes suggest that 6HS autografts are robust and durable, capable of withstanding the demands of daily activities and sports, thus enabling a more efficient and potentially faster rehabilitation process [33][34][35][36]. For instance, Yang et al [14] observed very low re-injury rates and high functional outcomes with 6HS autografts, emphasizing their clinical effectiveness. Additionally, recent studies, such as those by Chen et al [37], corroborated these findings, noting the biomechanical advantages and positive patient-reported outcomes associated with these larger grafts.…”
Section: Long-term Outcomes and Complicationsmentioning
confidence: 97%
“…High levels of patient satisfaction, improved quality of life, and notably low re-injury rates characterize the postoperative recovery of patients receiving 6HS autografts. Yang et al [14] highlighted the efficacy of 6HS autografts in achieving high knee functionality and significantly low re-injury rates, demonstrating their reliability in clinical practice. Recent clinical evaluations, like those by Ren et al [31], observed that patients with 6HS autografts tend to have a faster return to sports and a higher likelihood of regaining pre-injury activity levels compared to those with traditional four-strand grafts.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The length and size of the intact PCL in cases without PCL buckling are predictors of the length and size of the native ACL in adults. The use of this information to optimize graft diameter may lower the rates of ACL graft failure in the future [2].…”
Section: Introductionmentioning
confidence: 99%